PDEModelica1: a Modelica language extension for partial differential equations implemented in OpenModelica. (3rd April 2018) - Šilar, Jan; Ježek, Filip; Kofránek, Jiří
Abstract: Modelica is a language for modeling complex physical systems. It supports algebraic and ordinary differential equations. This paper presents a Modelica language extension for one-dimensional evolutionary partial differential equations (PDE) called PDEModelica1, which is based on earlier extensions, establishes several enhancements, and its support is implemented in OpenModelica. PDEs are solved using the method of lines. In this paper, we discuss changes to and enhancements of previous extensions as well as the numerical methods used. To conclude, we present a counter-current heat exchange model with results to demonstrate the applicability of our extension.